Pelatihan Da’I Muda Sumatera Utara - Syafaruddin Syafaruddin; Dira Nadira Amelia Siahaan; Muhammad Saleh Assingkily; Tarmiji Siregar (Universitas Islam Negeri Sumatera Utara, 2020)
Da'wah Islamiyah is the education of Islamic values which is taught through oral, written, and behavior or actions. To that end, Al-Ittihadiyah has responded to the need for da'wah cadres as “Islamic educators” in society by training the younger generation in training activities for young da'i. This paper aims to analyze the role of the DPW Al-Ittihadiyah in fostering young da'i in North Sumatra. The data were collected by means of interview techniques, observation, and documentation review. Furthermore, the data were analyzed using reduction techniques, data display, and conclusion drawing. The data validity was tested through triangulation and member check. The results of this study indicate that the role of Al-Ittihadiyah in fostering young preachers in North Sumatra has been carried out well through preachers' training every year since 2017. This is indicated by 3 aspects, namely (1) input in the form of efforts to produce young preachers. AlIttihadiyah through youth preachers training, (2) a process in the form of training activities with Islamic da'wah practices and materials for 3x24 hours, and (3) the output in the form of delegating young preachers to the Tanah Karo area for 7x24 hours.